Projeção retiniana, caracterização citoarquitetônica e neuroquímica da zona incerta do moco (Kerodon rupestris) - Morais, Paulo Leonardo Araujo de Gois (2014)
The Zona Incerta (ZI) is embryologically derived from the ventral thalamus, in continuity with the reticular nucleus of the thalamus. Studies usingneural tracers technics have allowed identify a complex connectional map including the ZI. Futhermore, cytochemical, molecular and functional data have shown abundant variability in the neurochemical contend in the ZI, as well as,the involvement of the ZI in the modulation of nociception, attention, alertness, control and maintenance of posture and control of visceral activity. This work aims to characterize the cytoarchitecture, neurochemical content of the ZI in the rock cavy (Kerodon rupestris), and a direct retinal-ZI pathway present in this species. The Nissl staining is effective for the delineation and characterization of ZI citoarchitecture. ZIc receives a contralateral retinal projection showing varicosities, suggesting a modulatory character of photic information. The ZI in the rock cavy, as in others rodents and primates, is characterized by a complex neurochemical signature. The ZI neurochemistry presents great diversity, especially in the medial portion of ZIr, where we have found immunoreactivity of all neuroactive substances investigated, and that NOS-IR, GFAP and CR helped the delimitation of middle ZI in ZId and ZIv. Nevertheless, just 5-HT-IR fibers are present in all subdivisions of the ZI. These data demonstrate the great wealth of the neurochemistry of rock cavy s ZI and a direct retinal modulation in the ZI, helping to explain it s broad functional repertory